Accounting For the Limited Success of #MeToo in the Popular Music and Stand-Up Comedy Industries - Worden, Chris; Gjika, Anna (Cultural Sociology, 2023)
Despite several high-profile cases and years of #MeToo activism, a lack of systemic change and consistent consequences for many alleged offenders has led journalists and fans to wonder when the popular music and stand-up comedy industries will truly have their ‘MeToo moment.’ In this article, we explain that this moment has already arrived, but has produced inconsistent results in these industries due to the unique cultural and structural obstacles they share, and which frustrate civil sphere actors’ attempts at civil repair. Our analysis draws on Jeffrey C. Alexander’s (2018, 2019) theory of societalization – the process by which institutional crises come to be seen as social problems that demand the intervention of civil sphere actors. We argue that where #MeToo and the popular music and stand-up comedy industries are concerned, the process of societalization has been (and will likely continue to be) ‘blocked’ or ‘stalled’ (Alexander, 2018, 2019). We suggest that the potential for societalization is reduced due to a combination of the arts sphere’s anti-civil values and weak institutionalization in the popular music and stand-up comedy industries.
Keywords: Bibliographie